PENGARUH ASET TETAP DAN MODAL KERJA TERHADAP LABA BERSIH PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Maulana, Jaka; Insani, Nabila Ramdhika Nurul (Universitas Logistik dan Bisnis Internasional, 2025)
Every company wants to increase company profits to attract investors so that the company must have financial reports. Companies in maintaining a stable financial statement condition to support company operations need a report, one of which provides details about fixed assets and working capital. This research intends to determine the effect between fixed assets and working capital on the company's net profit. Infrastructure sector companies registered on the Indonesia Stock Exchange (IDX). The method used method used in this study is a quantitative method with secondary data using the entities’ financial statement data and processed with IBM SPSS Statistic Version 27 with Normality Test, Product Moment Correlation, Multiple Correlation Analysis, Multiple Linear Regression Analysis, Coefficient of Determination, t test, and F test. The results of the t test in this study indicate that fixed assets partially have a positive and significant impact on net income, and working capital partially has a negative and insignificant impact on net income. The outcomes of the f test indicate that fixed assets and working capital simultaneously have a significant impact on net income